2021
DOI: 10.24839/2164-9812.eye26.1.20
|View full text |Cite
|
Sign up to set email alerts
|

What Skills Do Employers Seek? Four Perspectives

Abstract: online), is published quarterly by Psi Chi, the International Honor Society in Psychology. All contents ©2021 by Psi Chi. The pub li ca tion schedule fol lows the ac a dem ic year: fall, win ter, spring, and summer. All opinions ex pressed in signed ar ti cles are those of the author(s) and do not nec es sar i ly reflect those of the editors and/or Psi Chi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Since its publication in 2018, the SPS has been cited in articles concerning work and career-readiness skills (e.g., Appleby, Appleby, et al, 2019; Appleby, Young, et al, 2019; Collisson & Eck, 2022; Hard & RaoShah, 2022; Hettich, 2021; Troisi, 2021; Vespia et al, 2020), suggested as an integral component of undergraduate curricula (Spencer, 2019, 2021), and integrated into syllabi (Wickline, 2019). It has also informed the American Psychological Association (APA) Introductory Psychology Initiative’s (IPIs) recommendations for student transformation (Chew et al, 2022; Hard et al, 2022), been converted into a measurement used by others to help students self-assess their own skill development (Naufel, 2021, as cited by Troisi, 2021), and integrated into statistics and research methods courses (Wickline et al, 2021).…”
mentioning
confidence: 99%
“…Since its publication in 2018, the SPS has been cited in articles concerning work and career-readiness skills (e.g., Appleby, Appleby, et al, 2019; Appleby, Young, et al, 2019; Collisson & Eck, 2022; Hard & RaoShah, 2022; Hettich, 2021; Troisi, 2021; Vespia et al, 2020), suggested as an integral component of undergraduate curricula (Spencer, 2019, 2021), and integrated into syllabi (Wickline, 2019). It has also informed the American Psychological Association (APA) Introductory Psychology Initiative’s (IPIs) recommendations for student transformation (Chew et al, 2022; Hard et al, 2022), been converted into a measurement used by others to help students self-assess their own skill development (Naufel, 2021, as cited by Troisi, 2021), and integrated into statistics and research methods courses (Wickline et al, 2021).…”
mentioning
confidence: 99%